2016
DOI: 10.1016/j.cplett.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for reduced charge recombination in carbon nanotube/perovskite-based active layers

Abstract: Using impedance spectroscopy and computation, we show that incorporation of multiwall carbon nanotubes (MWCNTs) in the bulk of the active layer of perovskite-based solar cells reduces charge recombination and increases the open circuit voltage. An ~87% reduction in recombination was achieved when MWCNTs were introduced in the planar-heterostructure perovskite solar cell containing mixed counterions. The open circuit voltage (V oc) of perovskite/MWCNTs devices was increased by 70 mV, while the short circuit cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Two arcs can be identified at low forward bias. The arc at lower frequency is related to the charge recombination and the higher frequency one to the charge transfer at the interfaces of ETL/MAPbI 3 /Spiro‐OMeTAD configured devices . For the device with ZnO–MgO–EA + as ETL, while the transfer resistance ( R tr ) decreases significantly, the recombination resistance ( R rec ) increases remarkably.…”
mentioning
confidence: 99%
“…Two arcs can be identified at low forward bias. The arc at lower frequency is related to the charge recombination and the higher frequency one to the charge transfer at the interfaces of ETL/MAPbI 3 /Spiro‐OMeTAD configured devices . For the device with ZnO–MgO–EA + as ETL, while the transfer resistance ( R tr ) decreases significantly, the recombination resistance ( R rec ) increases remarkably.…”
mentioning
confidence: 99%
“…Figure c shows the Nyquist plots of the ZTO‐based PSC device compared with TiO 2 measured at applied bias voltages ( V app ) of 1.05 V under simulated AM 1.5 G solar illumination. In this condition, the internal electric field was significantly reduced, and charge transport was dominated by diffusion effect . Thus, the electronic transport component ( R elect ) was dominated by electron transport resistance ( R tr ) in the condition.…”
Section: Resultsmentioning
confidence: 94%
“…also introduced functionalized MWCNTs attached with poly(methyl methacrylate) end‐functionalized hexabenzocoronene into perovskite layers and investigated their impact on the charge recombination of the inverted p–i–n structured PSCs. [ 142 ] The PCE of the device containing 0.005 wt% MWCNTs increased from 12.0% to 12.9%. Impedance spectroscopy measurement confirmed that MWCNTs facilitated charge transportation and suppressed charge recombination in PSCs.…”
Section: Carbon Nanotubes In Perovskite Layersmentioning
confidence: 99%